1-Hydroxyethylidene-1, 1-diphosphonic acid used as pH-dependent switch to depress and activate fluorite flotation I: Depressing behavior and mechanism. (16th March 2020) - Wang, Jianjun; Li, Wenheng; Zhou, Zihan; Gao, Zhiyong; Hu, Yuehua; Sun, Wei
Graphical abstract: Highlights: HEDP used as pH-dependent switch to depress and activate fluorite flotation. Over 85% of calcite removed from mixed binary minerals at pH 6 using HEDP and NaOL. HEDP has a stronger chemical and hydrogen bonding interaction with fluorite. Abstract: Fluorite is usually separated from calcite by froth flotation method using large amounts of sodium silicate depressant, which can cause trouble in the loss of fluorite and wastewater treatment. In this study, green and low-cost 1-hydroxyethylidene-1, 1-diphosphonic acid (HEDP or H4 L) was used as pH-dependent switch to initially depress fluorite for calcite pre-removal at pH 6.0, and then activate fluorite for further upgrading fluorite concentrate at pH 8.0. The depressing behavior and mechanism were reported in this work. H2 L 2− was the dominant form of HEDP, and a stronger chemical adsorption of H2 L 2− on fluorite hindered the subsequent adsorption of sodium oleate (NaOL), while that of the calcite showed the opposite result. Two active O atoms in H2 L 2− could well match in interatom distance with two Ca sites on fluorite to form Ca-H2 L complexes. The pH-dependent switch reagent reported here may open a new avenue for more selective separation among mixed mineral systems.